ANALISIS SEMIOTIKA KEKERASAN TERHADAP ANAK DALAM FILM EKSKUL - Ismail Sam Giu; Susilastuti Dwi N; Basuki Basuki (Jurnal Ilmu Komunikasi, 2009)
This research to aim for knowing the representation symbol’s of children abuse on the Ekskul movie, and than for knowing the ideology’s meaning what was gived from this movie. Kind of this research is a qualitative interpretive research by using the analysis of semiotic method. The analysis of semiotic method is a research method to learn the questions of sign, until the sign give the means of something. This research used the analysis semiotic by Roland Barhes. The point of Barthes theory is order of signification. Barthes devide by two order of signification, denotation meaning and contation meaning. The file analysis is a explain descriptive of explora- tive aspect to represent and explain the phenomenon. The test of file validitation using source triangulation by interview the trusted informan, to confirm the analysis in this research. Founded from research result and by explained the all indicator below, finded the repre- sentation of Ekskul movie bring the ideology’s meaning from his producer, that is the message against of violent. Ekskul movie try to be aware us that’s the children abuse is exist and still going in our social life. Conscious it or not, like it or not, thats stil doing by the parents, teachers or the friends. Representation the symbol’s of violent is variation. That’s like striking stroke, ill-treatment, dressing-down, discrimination, let a way, and sexual violent.